Glorious (?) failure : catalogus - Coolens, Marc; De Graeve, Dieter; Gompertz, Will; Persijn, Jurgen (Duffel : Psychiatrisch Ziekenhuis, 2018)
In deze catalogus o.a. werk van Marcel Broodthaers, Marina Abramovic, Luc Tuymans, Banksy, Panamarenko, Thierry De Cordier, ...
Derde Triënnale Hedendaagse Kunst